Learner training in MALL: a Pakistani case study. Issue 2 (15th March 2021) - Rashid, Shaista; Howard, Jocelyn; Cunningham, Una; Watson, Kevin
ABSTRACT: This study investigated the effect of an innovative learner-training programme conducted with undergraduate students at a university in Pakistan. The MALL-based programme was designed to develop the students' competence and confidence in using smartphones to make blogposts as a means of increasing their opportunities to practice writing in English independently and beyond their educational setting. During the eight week programme, the 23 participants engaged in training in the use of technology for language learning purposes, in tandem with other technical, pedagogical and strategic training components to use their smartphones for writing blogposts. This report draws on data from pre- and post-programme surveys, interviews, written feedback, and blogpost output. The findings indicate that this combined learner-training model was successful in enhancing the participants' independent use of technology for English language practice. The programme also fostered their interest in learning more about new technologies and getting further training in using these for language learning. This study offers valuable insights for educators well beyond the Pakistani context, as it illustrates a model of learner training that can support students to utilize communicative affordances of readily available mobile devices for independent language learning.